2022
DOI: 10.4103/ijo.ijo_3145_21
|View full text |Cite
|
Sign up to set email alerts
|

Safety, efficacy, and patient selection of ripasudil in patients with uncontrolled glaucoma with maximum conventional medical therapy

Abstract: Purpose: Ripasudil hydrochloride hydrate (0.4%) is the first Rho-associated protein kinase (ROCK) inhibitor eye drop that lowers intraocular pressure (IOP) by increasing conventional aqueous outflow through the trabecular meshwork and Schlemm’s canal. We aimed to evaluate the safety and efficacy of ripasudil in patients using the maximum topical anti-glaucoma medications and with uncontrolled IOP. Methods: In our prospective interventional study, we enrolled 27 eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…The most common ocular adverse effects seen in patients receiving netarsudil/latanoprost in a fixed-dose combination were cornea verticillata (13.1%), conjunctival hyperemia (54.5%), and conjunctival hemorrhage (8.6%). 6 The most commonly seen ocular adverse effects of ripasudil were conjunctival hyperemia, allergic conjunctivitis, and blepharitis. 7 The difference in IOP found in all three groups after 7 days and after 15 days of treatment was clinically significant but not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The most common ocular adverse effects seen in patients receiving netarsudil/latanoprost in a fixed-dose combination were cornea verticillata (13.1%), conjunctival hyperemia (54.5%), and conjunctival hemorrhage (8.6%). 6 The most commonly seen ocular adverse effects of ripasudil were conjunctival hyperemia, allergic conjunctivitis, and blepharitis. 7 The difference in IOP found in all three groups after 7 days and after 15 days of treatment was clinically significant but not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Medical therapy could consist of switching the steroid to loteprednol or fluorometholone (as much as 45% reduction in IOP after substituting and/or adding a Rho kinase inhibitor [rho]), which has been shown to significantly reduce IOP (up to 33% reduction after failing maximum medical therapy). 1,2…”
Section: Rohit Krishna MDmentioning
confidence: 99%
“…The combination treatment resulted in significant IOP lowering at 1 month and 3 months. Jethva et al conducted a small prospective study in patients with inadequately controlled IOP on two or more treatments [29]; ripasudil was added to patients' ongoing glaucoma therapy, and the authors observed a significant reduction in IOP at 3 months. Furthermore, Tanihara et al found that ripasudil-brimonidine fixed-dose combination therapy was more effective than monotherapy of either drug and just as effective as administering ripasudil shortly followed by brimonidine, but with the added benefit of potentially improving patients' compliance [9].…”
Section: Ripasudil In Glaucomamentioning
confidence: 99%